EFFECT OF COLLABORATIVE LEARNING STYLE ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN BIOLOGY IN ORUMBA SOUTH LOCAL GOVERNMENT AREA (UNIZIK Journal of STM Education, 2024)
The study investigated on effect of collaborative learning style on secondary school students’ academic achievement in orumba south local government. Two research questions guided the study and three hypotheses were tested at 0.05 level of significance. Quasi- experimental design was used. Population of the study was 936 Senior Secondary school II students offering Biology in orumba south local government area. A sample of 87 SSII Biology students from two schools was obtained using simple random sampling technique. The instrument used for data collection was Biology Achievement Test (BAT), validated by two lecturers from Departments of Science Education and one lecturer from Educational Foundations all from Nnamdi Azikiwe University, Awka. Reliability was established using Kuder Richardson 20(KR-20) for BAT which yielded coefficient of 0.86. The data collected were analysed using mean and standard deviation for research questions while analysis of covariance was used to test the null hypotheses. Results indicated that collaborative learning improves secondary students' achievement and interest in Biology compared to conventional learning styles. Collaborative learning significantly influences achievement scores and interest levels, with no notable gender differences. While females show a greater increase in interest with collaborative learning, there is no significant interaction effect, suggesting universal benefits. These findings support a wider adoption of collaborative learning to enhance educational outcomes in Biology for all students.
Keywords: Biology Education, Collaborative learning style and Academic Achievement